2021
DOI: 10.1021/acs.joc.0c02937
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Dibenzothiophene Embedded Heteroporphyrins

Abstract: A series of new stable dibenzothiophene embedded heteroporphyrins were synthesized in 6–7% yields by condensing 1 equiv of dibenzothiophene-based tripyrrane with 1 equiv of four different diols, 2,5-bis(hydroxymethyl)­heterocycles (furan, thiophene, selenophene, and tellurophene), under mild acid-catalyzed conditions in CH2Cl2. The formation of dibenzothiophene embedded heteroporphyrins was confirmed by high-resolution mass spectrometry and thoroughly characterized by 1D and 2D nuclear magnetic resonance (NMR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…[11][12][13][14][15] In recent times, polyaromatic hydrocarbons/heterocycles (PAHs) were used in place of one or more pyrrole rings of porphyrinoids to generate a new type of polyaromatic embedded porphyrinoids with interesting electronic and coordination properties. [16,17] A perusal of literature revealed that the polyaromatic hydrocarbons/heterocycles such as biphenyl, [18] naphthalene, [19] phenanthrene, [20] fluorene [21,22] bipyridine, [23] phenanthroline, [24] dibenzofuran, [25] dibenzothiophene, [26] and phenothiazine [27] are few such polyaromatic hydrocarbons/heterocycles which have been introduced in place of one or more pyrrole rings of porphyrinoid framework and generated a wide range of very novel PAH embedded porphyrinoids. We used few of these PAH units such as dibenzofuran, dibenzothiophene, benzofuran, benzothiophene, fluorene and phenothiazine and synthesized very novel PAH embedded porphyrinoids which showed unique and interesting electronic and coordination properties.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] In recent times, polyaromatic hydrocarbons/heterocycles (PAHs) were used in place of one or more pyrrole rings of porphyrinoids to generate a new type of polyaromatic embedded porphyrinoids with interesting electronic and coordination properties. [16,17] A perusal of literature revealed that the polyaromatic hydrocarbons/heterocycles such as biphenyl, [18] naphthalene, [19] phenanthrene, [20] fluorene [21,22] bipyridine, [23] phenanthroline, [24] dibenzofuran, [25] dibenzothiophene, [26] and phenothiazine [27] are few such polyaromatic hydrocarbons/heterocycles which have been introduced in place of one or more pyrrole rings of porphyrinoid framework and generated a wide range of very novel PAH embedded porphyrinoids. We used few of these PAH units such as dibenzofuran, dibenzothiophene, benzofuran, benzothiophene, fluorene and phenothiazine and synthesized very novel PAH embedded porphyrinoids which showed unique and interesting electronic and coordination properties.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, we have reported some examples of tellurophene-containing porphyrinoids and among these, the [22]­telluradithiasapphyrins 10­(a–d) exhibit more interesting structural and electronic properties. We thought of synthesizing [22]­vacatadithiasapphyrins by extrusion of Te from [22]­telluradithiasapphyrins 10­(a–d) since these macrocycles 10­(a–d) are aromatic and showed very interesting structural, spectral, and redox properties and anticipated that such novel properties would be retained in [22]­vacatadithiasapphyrins (Chart ). Our attempts were successful in achieving stable aromatic vacatadithiasapphyrins.…”
Section: Introductionmentioning
confidence: 99%
“…2 In this respect, the carbaporphyrinoids embedding polycyclic aromatic hydrocarbon (PAH) subunits, namely aceneporphyrinoids, were found to be particularly intriguing, as it was demonstrated that the PAH motif is a crucial factor dictating the overall properties of the hybrid molecule. [3][4][5] The extent to which the electronic properties are altered depends on the nature of the PAH moiety present and whether it takes part in the p-delocalization with the rest of the macrocycle. In recent years aceneporphyrinoids have received a lot of attention due to their atypical p-conjugation, 6,7 their aromaticity varying from nonaromatic to antiaromatic, 8,9 and their ability to form stable organometallic complexes with metals of uncommon oxidation states.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the modication signicantly affects the electronic properties of the molecule, which in turn changes the spectral, structural, and coordination properties. 3,5,27 In a previous study, a new constitutional isomer of naphthiporphyrin was designed and synthesized, namely 28-hetero-2,7-naphthiporphyrin. 28 The compound was proven to act as a macrocyclic ligand, as demonstrated by the formation of organophosphorus(V) complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation